Role of social media and emerging digital technologies in shaping communication patterns, public discourse, and journalism - Aigerim Sultanova (Theoretical Hypotheses and Empirical Results, 2024)
This study explores the pivotal role of social media and emerging digital technologies in reshaping communication patterns, public discourse, and journalism, with a focus on policy implications. Employing qualitative methods, including literature review and content analysis, the research assesses how social media influences public opinion and economic decisions. Findings indicate that social media significantly shapes public opinion, with statistics showing increased online news consumption and a shift in news production towards more emotive, shareable content. The study emphasizes the need for policies that address the digital transformation’s impacts on societal communication and decision-making processes.communication environments and resilience among students.